Since distance is equal to rate times time:
Let x= the time traveled at 3 km/h
Let y= the time traveled at 4 km/h
We can say that
3x+4y=52
Or that three (kilometers) times the time traveled at 3 kilometers an hour plus 4 (kilometers) times the time traveled at 4 kilometers an hour is equal to 52; the total distance traveled.
Likewise, we can see that:
x+y=15
Because x, the number of hours traveled at 3 km/h added to y, the time traveled at 4 km/h is equal to 15; the total time traveled.
Now, I'll solve by substitution.
x=-y+15
Substitute that into the other equation.
3(-y+15) + 4y = 52
Distribute
-3y + 45 + 4y = 52
Combine like terms
y + 45 = 52
Minus 45 from both sides
y = 7
So Fredrick traveled at 4 km/h for 7 hours.
Now, to find the other value, substitute the value of y into one of the original equations.
x + 7 = 15
Minus 7
x = 8
So
Time traveled at 4 km/h = 7 hours
Time traveled at 3 km/h = 8 hoursSince distance is equal to rate times time:
Let x= the time traveled at 3 km/h
Let y= the time traveled at 4 km/h
We can say that
3x+4y=52
Or that three (kilometers) times the time traveled at 3 kilometers an hour plus 4 (kilometers) times the time traveled at 4 kilometers an hour is equal to 52; the total distance traveled.
Likewise, we can see that:
x+y=15
Because x, the number of hours traveled at 3 km/h added to y, the time traveled at 4 km/h is equal to 15; the total time traveled.
Now, I'll solve by substitution.
x=-y+15
Substitute that into the other equation.
3(-y+15) + 4y = 52
Distribute
-3y + 45 + 4y = 52
Combine like terms
y + 45 = 52
Minus 45 from both sides
y = 7
So Fredrick traveled at 4 km/h for 7 hours.
Now, to find the other value, substitute the value of y into one of the original equations.
x + 7 = 15
Minus 7
x = 8
So
Time traveled at 4 km/h = 7 hours
Time traveled at 3 km/h = 8 hours